Understanding and Calibration of Charge Storage Mechanism in Cyclic Voltammetry Curves. (21st August 2021) - Pu, Xiangjun; Zhao, Dong; Fu, Chenglong; Chen, Zhongxue; Cao, Shunan; Wang, Chunsheng; Cao, Yuliang
Abstract: Noticeable pseudo‐capacitance behavior out of charge storage mechanism (CSM) has attracted intensive studies because it can provide both high energy density and large output power. Although cyclic voltammetry is recognized as the feasible electrochemical technique to determine it quantitatively in the previous works, the results are inferior due to uncertainty in the definitions and application conditions. Herein, three successive treatments, including de‐polarization, de‐residual and de‐background, as well as a non‐linear fitting algorithm are employed for the first time to calibrate the different CSM contribution of three typical cathode materials, LiFePO4, LiMn2 O4 and Na4 Fe3 (PO4 )2 P2 O7, and achieve well‐separated physical capacitance, pseudo‐capacitance and diffusive contributions to the total capacity. This work can eliminate misunderstanding concepts and correct ambiguous results of the pseudo‐capacitance contribution and recognize the essence of CSM in electrode materials. Abstract : Well‐separated physical capacitance, pseudo‐capacitance, and diffusive capacity are achieved from the CV curves of typical electrode materials for metal‐ion batteries after three successive treatments including de‐polarization, de‐residual and de‐background as well as non‐linear fitting calculation, offering a more rational and reliable method to calculate the pseudo‐capacitance contribution.